Gut dysbiosis and the clinical spectrum in anti-Ro positive mothers of children with neonatal lupus. (31st December 2022) - Clancy, Robert M.; Marion, Miranda C.; Ainsworth, Hannah C.; Chang, Miao; Howard, Timothy D.; Izmirly, Peter M.; Masson, Mala; Buyon, Jill P.; Langefeld, Carl D.
ABSTRACT: Anti-SSA/Ro antibodies, while strongly linked to fetal cardiac injury and neonatal rash, can associate with a spectrum of disease in the mother, ranging from completely asymptomatic to overt Systemic Lupus Erythematosus (SLE) or Sjögren's Syndrome (SS). This study was initiated to test the hypothesis that the microbiome, influenced in part by genetics, contributes to disease state. The stool microbiome of healthy controls (HC) was compared to that of anti-SSA/Ro positive women whose children had neonatal lupus. At the time of sampling, these women were either asymptomatic (Asym), had minor rheumatic symptoms or signs considered as an undifferentiated autoimmune syndrome (UAS), or were diagnosed with SLE or SS. Differences in microbial relative abundances among these three groups were tested assuming an ordering in clinical severity (HC<Asym/UAS<SS/SLE) and then again without the ordinal assumption. Those taxa that showed differential relative abundances were then tested for whether the effect size differed depending on the women's HLA SLE-risk allele genotype (DRB1*03:01, DRB1*15:01, DQB1*02:01 and DQB1*06:02) or anti-SSA/Ro autoantibody levels. Multiple genera within the families Ruminococcaceae and Lachnospiraceae showed evidence of an HLA-by-genus interaction (P < .05). Four genera exhibited evidence of an interaction with anti-Ro52 IgA: Lachnoclostridium, Romboutsia, Bacteroides and Actinomyces (P < .01). In addition to documenting differences in microbial relative abundances across clinical severity of disease, these data provide a first-time demonstration that microbial differences are correlated with HLA SLE-risk alleles. Taken together, these data suggest that the clinical spectrum from benign to overt clinical autoimmunity may partially result from or trigger a complex interplay among specific microbial profiles, anti-Ro autoantibodies, and genetics.